2016
DOI: 10.1017/s0033291716002154
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic burden in schizophrenia and ability to benefit from psychosocial treatment programmes: a 3-year prospective cohort study

Abstract: Anticholinergic burden has a significant impact on patients' ability to participate in and benefit from psychosocial treatment programmes. Physicians need to be mindful of the cumulative effect that medications can have on patient cognition, functional capacity and ability to benefit from psychosocial treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…O’Reilly et al recently reported that anticholinergic burden negatively impacted the outcomes of psychosocial treatment focusing on cognitive impairment in patients with schizophrenia (O’Reilly et al, 2016). Because cognitive impairment related to anticholinergic burden may affect skills necessary for independent living and vocational success, it is important for clinicians to appreciate the cumulative effects of anticholinergic drug regimen properties on cognition.…”
Section: Discussionmentioning
confidence: 99%
“…O’Reilly et al recently reported that anticholinergic burden negatively impacted the outcomes of psychosocial treatment focusing on cognitive impairment in patients with schizophrenia (O’Reilly et al, 2016). Because cognitive impairment related to anticholinergic burden may affect skills necessary for independent living and vocational success, it is important for clinicians to appreciate the cumulative effects of anticholinergic drug regimen properties on cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials in this field are difficult and there are few available as guides [ 12 , 13 ]. Paradoxically pharmacotherapy may compromise the effectiveness of psychosocial interventions to some extent by impairing neurocognition and functioning [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 There is already evidence that symptoms are related to neurocognitive changes 2 and that neurocognitive impairments influence the behavioural handicaps of schizophrenia 3 and treatment responses. 4 Functional mental capacity is often used to refer to functional decision-making abilities required by a patient to make legally competent decisions about their care. 5 Cross-sectional studies show that between 43.8% 6 and 60% 7 of patients admitted to a psychiatric hospital lack treatment-related functional decisional capacity at a given time.…”
mentioning
confidence: 99%